Microwave Doppler Radar Occupancy Sensing for HVAC Energy Savings - Amy Droitcour; Shekh M. M. Islam; Ryan Neville; Miles Topping; Eileen Peppard; Victor M. Lubecke; Olga Boric-Lubecke (IEEE Journal of Microwaves, 2024)
Buildings consume about 30% of the world's energy, and produce 37% of global energy-related CO2 emissions. Building energy efficiency is becoming even more critical as climate change related events take a toll on human life, and further increase building energy consumption due to higher cooling needs. Reducing building energy consumption is imperative to break this detrimental cycle of harmful emissions creating more energy demand. Occupancy sensors play a crucial role in building energy efficiency by optimizing the operation of lighting, heating, ventilation, air conditioning (HVAC) and other systems based on the presence or absence of people. Microwave radar-based occupancy sensors offer improved accuracy, versatility, and coverage range over other occupancy sensors, while remaining non-intrusive and low-cost. However, building energy savings from usage of radar-based occupancy sensors has not been widely documented. Here, we show that microwave occupancy sensors, installed in an academic office building in Hawai'i can be used to manage HVAC schedules, ultimately providing energy savings of over 6 kWh/yr/sf, about 20% reduction in energy usage for this building. These results demonstrate how controlling energy consumption based on microwave occupancy sensing can greatly reduce building energy consumption which is crucial for controlling climate change.